PENERAPAN SCAFFOLDING DALAM MENINGKATKAN PEMAHAMAN MATEMATIKA PADA MATERI PECAHAN SISWA KELAS IV SD N BULAKREJO 3 - Nugrahani, Ahmad Naharudin Nugroho, Al Verdad Cadhika Agustino , Bella Kusumawati, Diah Arum Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In learning mathematics, there are many challenges when conducting the learning process. In fact, many students have difficulty in understanding the concept of learning mathematics with a scaffolding approach. The purpose of this study was to improve students' understanding with this approach in mathematics subjects on fraction material. The type of research used is Classroom Action Research (PTK). The subject of this research is the fourth grade students of SD N Bulakrejo 3 which totalled 29 people, consisting of 18 female students and 11 male students. While the object of this research is student learning activity. Data collection was done by observation technique. Data on student understanding in this study was collected by filling out observation sheets by teachers who taught in class. This research was conducted on learning Mathematics Fraction material using II cycles, where each cycle consists of four stages, namely the planning, implementation, observation, and reflection stages of learning. The results of the research conducted in class IV SDN Bulakrejo 03, the application of scaffolding strategies consistently succeeded in improving the quality of students' mathematics learning